Association between choroid plexus volume, brain atrophy and lesion load measures in multiple sclerosis - Rumbin, Sofia (My University, 2026)
Multiple sclerosis (MS) is the most common chronic neuroinflammatory disease affecting young adults, leading to neurological disability and cognitive impairment. Pathologically, MS is characterized by demyelinating white matter lesions (WMLs), gliosis and neuroaxonal loss within the central nervous system (CNS), facilitated by immune cell infiltration into CNS. The number and location of WMLs determine the symptoms experienced by individuals, as well as the severity of clinical disability. Recent studies have reported that choroid plexus (CP) volume is significantly larger in people with MS (pwMS) compared to healthy controls (HCs). CP is a highly vascularized tissue located within the brain ventricles and is primarily responsible for the production and secretion of cerebrospinal fluid (CSF). It has also been suggested to serve as a pathway for immune cell entry into the CNS, playing a vital role in MS pathology. CP has shown several structural and functional alterations in MS, leading to abnormal CSF production and impaired glymphatic function, as well as increased microglial activity and release of pro-inflammatory cytokines. Interest in the relationship between CP enlargement and MS has increased in recent years. CP enlargement has been associated with increased lesion load and greater brain atrophy in pwMS, particularly in periventricular regions. Furthermore, CP enlargement has been correlated with greater clinical disability and cognitive impairment in pwMS. Taking these observations together, enlargement of CP has been suggested to enhance chronic, smouldering inflammation within the CNS. This review will discuss the association between CP volume, brain atrophy and lesion load measures in MS, as well as their relationship to chronic neuroinflammation.
Keywords: multiple sclerosis, choroid plexus, white matter lesions